Innovative Victoria Park Tunnel design is Communicated Effectively to Stakeholders with the Aid of Three-Dimensional Visualisation Medi - M Sparrow (The Australasian Institute of Mining and Metallurgy, 2011)
The Victoria Park Tunnel project is an inner-city alliance project in central Auckland, New Zealand. The existing two-directional viaduct will be modified to single-direction flow, and a new northbound 440 m cut and cover tunnel will be constructed beneath Victoria Park. Three-dimensional (3D) visualisation media were used to communicate key design innovations to stakeholders and the general public. The 3D visual material has proven a useful tool for informing motorists of a new safety barrier method adopted for traffic management.This presentation will explain how 3D visualisation was incorporated in the project and will showcase the 3D visualisation media created for the project.